HALAL HARAM DALAM PERSPEKTIF PENDIDIKAN (Kajian Hadis Tahlili) - Mosiba, Risna (Inspiratif Pendidikan, 2018)
Rasulullah saw. educate the people well, by making various parables and explaining them. We can understand this from various traditions. In Islamic law, halal and haram issues are very clear. While the vague is only known by some people about the law and its arguments. When a case is not clear to humans, whether halal or haram, then it should be avoided until it becomes clear to him that the case is halal or haram. Be careful (and keep away) from the shubhat matters is an effort to guard one's self over his religious faith and guard against his pride from reproaches. In fact, someone, if he falls into the matter of syubhat, he will easily underestimate matters that are clearly the law of his prohibition.